PENGGUNAAN MEDIA SOSIAL SEBAGAI TREND MEDIA DAKWAH PENDIDIKAN ISLAM DI ERA DIGITAL - Wibowo, Adi (JURNAL ISLAM NUSANTARA, 2019)
This paper seeks to explain the trend of da'wah in the digital age with the use of social media, this media makes many preachers intrigued to channel their da'wah by utilizing the internet facilities of millennial preachers to create Islamic content that is casually packaged in everyday life stories and spiced with things the funny thing, this strategy attracts millions of viewers proven in the description of the number of viewers on YouTube. Da'wah is one of the activities aimed at inviting others in kindness, reminding someone of the end of the day, while preaching media is a tool for inviting others to better paths. An-nawawi boarding school playing purworejo is one of the halls that implement the preaching strategy by utilizing social media such as: Instagram and Youtube which are packaged with the latest trends in the form of images and videos that target millennials, this is done because of the increasingly widespread social media accounts which tends to be radical even contaminated by Isis which easily punishes haram without first reviewing the determination of the correct fiqh rules. This study uses a case study of the responses of students who are in the boarding boarding an-nawawi boarding school purworejo to preaching messages contained in social media content Instagram, facebook, twitter and Youtube Pondok An Nawawi boarding school in Purworejo.